Flash Pro CS5 : video quickstart guide - Chun, Russell (Peachpit Press, 2010)
"Learn Flash Professional CS5 the quick and easy way with almost two full hours of video training from bestselling author Russell Chun. Get expert guidance on using the powerful new tools and important features in Flash Professional CS5"--Resource description page.